Aspek Hukum Ganti Rugi Atas Dampak Pencemaran Lingkungan Oleh Industri - Cholilah Hanum (Jurnal Interpretasi Hukum, 2025)
This study is entitled "Legal Aspects of Compensation for the Impact of Environmental Pollution by Industry" which aims to examine three main problem formulations, namely: (1) the legal consequences of environmental pollution according to Law No. 32 of 2009 concerning Environmental Protection and Management; (2) the process of accountability in providing compensation for environmental pollution according to the Law; and (3) efforts made by the Environmental Service of Mandailing Natal Regency in preventing environmental pollution in the community. This study uses a normative legal method, namely legal research that focuses on the study of norms or legal rules that apply in laws and regulations, as well as relevant literature. This study aims to systematically and comprehensively analyze the application of law to the problems faced. The results of the study indicate that the legal consequences of environmental pollution according to Law No. 32 of 2009 include administrative, criminal, and civil sanctions. Efforts made by the Environmental Service of Mandailing Natal Regency involve an educational approach to the community, supervision of industry, and law enforcement against environmental violations